2019
DOI: 10.1080/1360080x.2019.1658839
|View full text |Cite
|
Sign up to set email alerts
|

Size matters: an analysis of UK higher education institution mission statements

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The mission statements of public universities ranged between 29 and 366 words, with an average of 91.6 words, and the mission statements for 23 public universities contained fewer than 100 words (71.8%), suggesting that the mission statements of public universities are more concise. This finding is in line with Flavin et al (2020), who concluded that the length of the mission and the type of institution are correlated. This correlation may be a result of public missions being more aligned with state regulations, whereas private universities can be more specific.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The mission statements of public universities ranged between 29 and 366 words, with an average of 91.6 words, and the mission statements for 23 public universities contained fewer than 100 words (71.8%), suggesting that the mission statements of public universities are more concise. This finding is in line with Flavin et al (2020), who concluded that the length of the mission and the type of institution are correlated. This correlation may be a result of public missions being more aligned with state regulations, whereas private universities can be more specific.…”
Section: Resultssupporting
confidence: 91%
“…Researchers have studied the main components of a mission statement and its optimal components in relation to different types of organizations. For this, studies and evaluation frameworks have been used to carry out qualitative and quantitative research in different organizations (Guimarães et al , 2020; Flavin et al , 2020; Berghaeuser and Hoelscher, 2020; Arias-Coello et al , 2020; Dumanig and Symaco, 2020; Giusepponi and Tavoletti, 2018). In addition, researchers have analyzed mission statements published on the internet by different organizations through content analysis (Cortés-Sánchez, 2017; Deus et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of their mandate, Russell Group universities tend to display a lower tendency towards the development of sector-specific focus and programming. Although the present study does not deny that non-Russell Group universities might include retail-focused programmes in their education offering, this research focuses on Russell Group universities because they have a (1) widely understood (brand) identity, (2) high reputation of quality and (3) high market proposition (Flavin et al , 2019; Rutter et al , 2016), and accordingly, are expected to account for a wide proportion of the supply of retailing skills on the job market.…”
Section: Supply Of Retail Expertisementioning
confidence: 98%
“…While most universities have mission statements for the institution at large (Flavin, Zhou Chen, & Quintero, 2020), these may not clearly or easily translate to local decisions. More valuable are local mission statements for teams or departments, which are more specific to their particular operation (Meacham & Gaff, 2006).…”
Section: The Case For Local Mission Statementsmentioning
confidence: 99%